The Effect of Diabetes Regulation on Platelet Release, Fibrinolysis and Coagulation Tests, Before and After Stimulation with DDAVP - Knaap, J H v d; Boer, A C de; Pannebakker, M A G; Heerde, W van; Ottolander, G J H den (Thrombosis and Haemostasis, 1985)
In this longitudinal study we measured β-TG, PF4, fibrinolytic activity (extrinsic and euglobulin fraction), fibrinogen, FVIII RAg and FVIII Rcof before and after i.v. DDAVP (FPA was only measured before DDAVP) in 20 patients with diabetes mellitus. These parameters were measured on three occasions: phase I: during disregulation, phase II: after three weeks of strict control, phase III: after nine weeks of good control. Twenty-two healthy volunteers served as normal controls.No significant differences related to metabolic control were found for β-TG, PF4, FPA and fibrinogen. There was no change after i.v. DDAVP administration. Fibrinolytic activity showed a significant increase after i.v. DDAVP. Baseline values and post-DDAVP increase were not significantly different from our normal controls.FVIII RAg and FVIII Rcof were both significantly elevated in diabetes mellitus. Both increased significantly after DDAVP. The FVIII RAg release (ΔFVIII RAg) was significantly less in the diabetics. Fibrinolytic activity, FVIII RAg and FVIII Rcof are independent of the degree of metabolic control in patients with diabetes.
Keywords: Platelets; Fibrinolysis; Coagulation tests; Fibrinolysis; Diabetes mellitus; DDAVP